Study of strontium hexaferrite prepared by solid state reaction using celestite and hematite - J. B. Neto; C. H. N. Cordeiro; M. M. de Góis; J. Xavier; J. M. Soares (Physics and Chemistry of Minerals, 2026)
Strontium hexaferrite (SrM) powders were prepared by solid-state reaction using celestite and magnetite/hematite. Energy dispersive X-ray fluorescence spectrometry, X-ray diffractometry (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometry were used for analyses. The precursor ores were purified by hand-sorting and magnetic separation. Magnetic separation yielded 75% magnetite and 25% hematite in iron ore. Strontium reached a single phase of $$\rm SrSO_4$$ via hand-sorting. XRD confirmed single-phase $$\rm SrFe_{12}O_{19}$$ sample with hexagonal symmetry (space group $$\rm P6_{3}/mmc$$ ). EDS analyse confirmed that the percentage of elements is in agreement with the expected stoichiometry for the hexaferrite phase. Initial SrM sample exhibited magnetization at maximum field of $$\rm 56~emu/g$$ and coercive field of $$\rm 632~Oe$$ . Although remanence and coercivity were lower than expected for the initial SrM sample, due to wide particle size distribution observed in SEM images, by optimizing synthesis parameters, particularly annealing at $$950^° $$ C, the coercivity increased by nearly eightfold, reaching 4.96 kOe. The sample annealed at 950 $$^° $$ C also exhibited a maximum energy product of $$\rm (BH)_{max}≈ 3.20~MGOe$$ and an estimated magnetocrystalline anisotropy constant of $$\rm K_1\sim 3.6× 10^6~erg/cm^3$$ . Microstructural evidence confirmed the predominance of particles in the monodomain regime, which justifies the increase in the coercive field. The results demonstrate that microstructural control is decisive for tuning the magnetic response of SrM, enabling the large-scale viability of this synthesis route for the production of high-coercivity hexaferrites, using a direct mixture of minerals instead of conventional industrial reagents.

The anterograde tarsal venography enhances vessel visualization compared to the retrograde approach in horses - Daniel L. Parra-Torres; Gabriel B. Melo-Neto; Hector O. Garcia; Ana Paula A. Souza; Emanuel Vitor P. Apolonio; Celso Antônio Rodrigues; Ana Liz G. Alves; Carlos Alberto Hussni; Marcos J. Watanabe (The Veterinary Journal, 2026)

Repellent activity and toxicity of the essential oil of Calyptranthes concinna DC. using the model insect Drosophila melanogaster - M. S. Costa; T. S. Freitas; M. A. S. Oliveira; N. J. S. Araujo; S. P. Silva; Z. S. Silveira; N. S. Macêdo; J. C. Andrade-Pinheiro; H. S. Santos; A. M. R. Teixeira; F. A. B. Cunha; Ivo C. Pita Neto; et al. (Brazilian Journal of Botany, 2026)
Insects, belonging to the phylum Arthropoda, play essential roles in ecosystems, play essential roles in ecosystems, such as pollination, pest control, and decomposition. However, some species are vectors of diseases, which makes the development of control methods crucial. The use of synthetic insecticides, although effective, causes serious environmental and health problems. As an alternative, plant essential oils, which are biodegradable and can have repellent and toxic effects on insects, have gained prominence. This study focuses on the species Calyptranthes concinna DC., belonging to the Myrtaceae family, whose repellent and toxicological properties were evaluated using Drosophila melanogaster Meigan (1830) as an experimental model. The botanical material of Calyptranthes concinna was collected from the Private Natural Heritage Reserve in Palmeira-PR, and the essential oil was extracted from the dried leaves by hydrodistillation. The oil, with a yield of 0.26%, was stored for later analysis. The species Drosophila melanogaster was used as a model for toxicity and repellent activity tests. The tests involved fumigation of flies with different doses of oil, evaluation of damage to locomotor capacity and repellency test using filter paper. Data were analyzed statistically using two-way ANOVA. Calyptranthes concinna essential oil demonstrated low toxicity to Drosophila melanogaster , with 100% survival at all concentrations tested over 48 h and deaths that were not statistically significant compared to the water control. Impairment of locomotor capacity was observed only at the highest concentrations (40 µg/mL) after 3 h, and at intermediate concentrations (20 µg/mL) after 6 h, but these effects were equal to the control after 12 h. The repellency test revealed that the essential oil has a significant efficacy, especially at higher concentrations (39 µg/cm 2 ), comparable to the commercial repellent DEET, indicating that C. concinna essential oil is a promising alternative to synthetic repellents. Calyptranthes concinna essential oil has demonstrated potential as a natural repellent, with low toxicity and efficacy comparable to commercial DEET. Compared to studies with other essential oils and similar compounds, C. concinna oil has shown consistent results, suggesting that it may be an effective and environmentally friendly alternative to synthetic repellents. The presence of terpenes in the essential oil may be related to its repellent effect. These results support the use of C. concinna essential oil as a promising natural repellent.

Prospection of Autochthonous Lactic Acid Bacteria Displaying Probiotic Potential to Enhance Colossoma macropomum Larvae Growth and Immunoprotection Against Aeromonas hydrophila - Thayná M. dos Santos; Layana A. B. Pereira; Laine P. C. dos Santos; Andrya L. Lopes; Larissa A. F. Sampaio; Graziella V. G. de Matos Silva; Juliana N. Ferreira; Gleika T. J. Dos Reis; Jonny B. Teixeira; Raimundo J. T. Diniz‐Neto; Laura G. M. de Carvalho; Michelle Midori Sena Fugimura; et al. (Journal of Fish Diseases, 2026)
This study assessed the functional potential of autochthonous lactic acid bacteria isolated from the gastrointestinal tract of tambaqui ( Colossoma macropomum ) as larviculture probiotics. Five strains were selected and identified as belonging to the genus Weissella . In vitro assays revealed high tolerance to acidic pH (2.0–3.0), resistance to bile salts (10%), biofilm formation capacity, hydrophobicity and direct Aeromonas hydrophila inhibition. In in vivo tests, strains M13 and M14 promoted significant increases in tambaqui survival (72.2% and 68.7%; p

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Intrauterine growth restriction (IUGR) modifies the hypothalamic response to a systemic glucose load in adult male rats, as assessed by proteomic analysis - Thais A. J. Mutran; Amanda P. Pedroso; Adriana P. de Souza; Valter T. Boldarine; Antonio M. M. Neto; Claudia B. Angeli; Lila M. Oyama; Giuseppe Palmisiano; Eliane B. Ribeiro; Monica M. Telles (Metabolic Brain Disease, 2025)

Biosorption assessment of emerging contaminants onto acidogenic and methanogenic biofilm reactors: Influence of lipophilic and electrostatic interactions - Rodrigo B. Carneiro; Paula Y. Takeda; Maria E.S. Dias; Elis W. Nogueira; Marcelo Zaiat; Álvaro J. Santos-Neto (Journal of Environmental Chemical Engineering, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

When zombies go vegan: Ophiocordyceps unilateralis hosts are selecting to bite palm leaves before dying? - Fernando S. Andriolli; J. Aragão Cardoso Neto; Paul V.A. Fine; Diego Salazar; Giovanna Figueroa; Diego V. Torres; J. Wellington de Morais; Fabricio B. Baccaro (Acta Oecologica, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Biotransformation pathways of pharmaceuticals and personal care products (PPCPs) during acidogenesis and methanogenesis of anaerobic digestion - Rodrigo B. Carneiro; Rubén Gil-Solsona; Jessica Subirats; Esteban Restrepo-Montes; Marcelo Zaiat; Álvaro J. Santos-Neto; Pablo Gago-Ferrero (Journal of Hazardous Materials, 2024)

Investigation of Rabies virus in wild mammals of the atlantic forest in Rio de Janeiro, Brazil - M. Cocchi; C. M. Barboza; J. G. Garcia; R. M. Zamudio; A. Champi; R. L. M. Novaes; S. F. Costa-Neto; R. Moratelli; H. B. C. R. Batista (Brazilian Journal of Microbiology, 2024)

Optimizing ReBreed21 II: Fertility and reproductive efficiency in different parities during a shortened breeding season in beef cattle - João Paulo N. Andrade; Pedro J.L. Monteiro; Alexandre B. Prata; Adelino J. Robl; José Neto; Beatriz Lippe; Heuller S. Ribeiro; Diego Hartmman; Roberto Sartori; Milo C. Wiltbank (Theriogenology, 2024)

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Anaerobic co-metabolic biodegradation of pharmaceuticals and personal care products driven by glycerol fermentation - Rodrigo B. Carneiro; Gisele M. Gomes; Franciele P. Camargo; Marcelo Zaiat; Álvaro J. Santos-Neto (Chemosphere, 2024)

Optimizing PtSn Composition in Direct Sugarcane Extract Fuel Cells: A Sustainable Bioenergy Solution - Bruno D. Q. Villardi; Victoria A. Maia; Julio Nandenha; Priscilla J. Zambiazi; Rodrigo F. B. de Souza; Almir O. Neto (Sugar Tech, 2024)

Ex vivo inhibition of PGE2 formation in human blood by four bicyclico [3.2.1] octane neolignans isolated from Aniba firmula bark, two with unusual structural pattern - Mario F. C. Santos; Karen de J. Nicácio; Albert Katchborian-Neto; Miller S. Ferreira; Daniel de Oliveira Miranda; João V. Andrade; Herinque de A. Pereira; Ester Gonçalves de Jesus; Thamires B; Silva Souza; Raquel P. Morais-Urano; Danielle Ferreira Dias; et al. (Natural Product Research, 2024)

The deep dive of organohalogen compounds: Bioaccumulation in the top predators of mesopelagic trophic webs, pygmy and dwarf sperm whales, from the Southwestern Atlantic ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Vitor L. Carvalho; Letícia Gonçalves; Pedro V. de Castilho; Eduardo R. Secchi; Silvina Botta; Milton C.C. Marcondes; Adriana C. Colosio; Marta J. Cremer; Haydée A. Cunha; et al. (Chemosphere, 2023)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

United we stand, divided we fall: in-depth proteomic evaluation of the synergistic effect of Mo -CBP 3 -PepI and Ciprofloxacin against Staphylococcus aureus biofilms - Nilton A. S. Neto; Tawanny K. B. Aguiar; Rayara J. P. Costa; Felipe P. Mesquita; Lais L. B. de Oliveira; Maria E. A. de Moraes; Raquel C. Montenegro; Rômulo F. Carneiro; Celso S. Nagano; Cleverson D. T. Freitas; Pedro F. N. Souza (Biofouling, 2023)

Identification of potential new mosquito-associated viruses of adult Aedes aegypti mosquitoes from Tocantins state, Brazil - Matheus A. Duarte; Fabrício S. Campos; Osvaldo F. Araújo Neto; Leonardo A. Silva; Arthur B. Silva; Thalita C. Aguiar; Raissa N. Santos; Ueric J. B. Souza; Giselly B. Alves; Fernando L. Melo; Daniel M. P. Ardisson-Araujo; Raimundo W. S. Aguiar; et al. (Brazilian Journal of Microbiology, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Additional Pressure to a Threatened Species: High Persistent Organic Pollutant Concentrations in the Tropical Estuarine Batoid Gymnura altavela - L. G. Paiva; M. Vannuci-Silva; B. Correa; E. Santos-Neto; M. Vianna; J. L. Lailson-Brito (Bulletin of Environmental Contamination and Toxicology, 2021)

Potentiation of Antibiotic Activity by a Meldrum’s Acid Arylamino Methylene Derivative against Multidrug-Resistant Bacterial Strains - Maria M. C. da Silva; José B. de Araújo-Neto; Ana C. J. de Araújo; Priscilla R. Freitas; Cícera D. de M. Oliveira-Tintino; Iêda M. Begnini; Ricardo A. Rebelo; Luiz E. da Silva; Sandro L. Mireski; Michele C. Nasato; Maria I. L. Krautler; Jaime Ribeiro-Filho; et al. (Indian Journal of Microbiology, 2021)

Reduced cutaneous inflammation associated with antioxidant action after topical application of the aqueous extract of Annona muricata leaves - Luana M. Cercato; Jéssica M. D. Araújo; Alan S. Oliveira; Allan J. O. Melo; Bruno S. Lima; Edmilson W. P. dos Santos; Agenor G. dos S. Neto; Ricardo L. C. de Albuquerque-Júnior; Marcelo C. Duarte; Adriano A. S. Araujo; Ana Mara O. Silva; Renata Grespan; et al. (Inflammopharmacology, 2021)

Evaluation of bioavailability of trace metals through bioindicators in a urbanized estuarine system in southeast Brazil - K. S. Vieira; M. A. C. Crapez; L. S. Lima; J. F. Delgado; E. B. C. C. Brito; E. M. Fonseca; J. A. Baptista Neto; V. M. C. Aguiar (Environmental Monitoring and Assessment, 2021)

Correction to: α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Neotropical endemism and dispersal events between tropical and extra‐tropical regions underlay the reticulate assemblages of muscid flies - Peter Löwenberg‐Neto; Claudio J. B. de Carvalho (Journal of Biogeography, 2020)
Aim The housefly family Muscidae originated during the Paleocene–Eocene and is currently distributed worldwide. We investigated how muscid genera have assembled in the continents by historical dispersal events. Location Global (except Antarctica). Taxon Muscidae, Diptera, Insecta. Methods We compiled a dataset of 181 species, which provided geographic information for 67 genera as terminals. Phylogenetic and geographic data were fitted by five dispersal–extinction–cladogenesis models based on dispersal constraints. Based on the event inferences of the best‐fit model, we quantified the direction and frequency of dispersals through time in absolute numbers and in relation to the number of lineages. Results The best‐fit model was ‘unrestricted routes’, which inferred 48 events of dispersals: 66% were trans‐climatic events and 81% were transoceanic events. The direction of the dispersals was strongly asymmetric: the Neotropical (NEO) region was the primary source of lineages for all other regions and the Palearctic (PAL) was the secondary source. The relative frequency of dispersal events through time plot was marked by three phases: the early peak of the frequency (40–35 million years ago [Ma]), a valley of low frequencies (30–20 Ma), and the recent peak (15–5 Ma). Trans‐climatic dispersals from the NEO to the PAL region occurred in all phases. Lineages of the Cyrtoneurininae showed a low frequency of dispersal events and most of the terminals (11 of 15) were endemic to the NEO region. Conclusion The Muscidae family originated in the Neotropical region and more recent dispersal events to the Palearctic region established the scenario for lineages to diversify and spread worldwide. Trans‐climatic dispersals were more frequent than cis‐events and tropical niche conservatism was not the underlying mechanism for the whole clade. We showed that dispersal events between biogeographic regions of the same and different climatic zones were required to achieve the current distribution of extant genera of muscids across the globe.

Effect of Additives to Improve Calcium-Based Sorbents in Semi-Dry Flue Gas Desulphurization - Ítalo W. L. França; Samuel J. M. Cartaxo; Moises Bastos-Neto; Luciana R. B. Gonçalves; Fabiano A. N. Fernandes (Emission Control Science and Technology, 2020)

Natural Vs Managed Habitat: Effect Over the Seed-Predator Pachymerus nucleorum and Its Natural Enemies - J O S Silva; M L E Costa; B S Paixão; J D B Macêdo; P M S Rodrigues; E M F Lins-Neto (Neotropical Entomology, 2020)

Which Species of Coconut Moth Occurs in Brazil: Atheloca subrufella vs. Atheloca bondari (Lepidoptera: Pyralidae)? - A A Paz-Neto; M. T. S. Freitas; M. G. C. Gondim; J. W. S. Melo; R. B. Querino; V. Q. Balbino (Neotropical Entomology, 2019)

The citrus flavanone naringenin attenuates zymosan-induced mouse joint inflammation: induction of Nrf2 expression in recruited CD45+ hematopoietic cells - Allan J. C. Bussmann; Sergio M. Borghi; Tiago H. Zaninelli; Telma S. dos Santos; Carla F. S. Guazelli; Victor Fattori; Talita P. Domiciano; Felipe A. Pinho-Ribeiro; Kenji W. Ruiz-Miyazawa; Antonio M. B. Casella; Josiane A. Vignoli; Doumit Camilios-Neto; et al. (Inflammopharmacology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

A Review of High Impact Weather for Aviation Meteorology - Ismail Gultepe; R. Sharman; Paul D. Williams; Binbin Zhou; G. Ellrod; P. Minnis; S. Trier; S. Griffin; Seong. S. Yum; B. Gharabaghi; W. Feltz; M. Temimi; et al. (Pure and Applied Geophysics, 2019)

Studies of NMR, molecular docking, and molecular dynamics simulation of new promising inhibitors of cruzaine from the parasite Trypanosoma cruzi - Renato A. Costa; Jorddy N. Cruz; Fabiana C. A. Nascimento; Sebastião G. Silva; Silvana O. Silva; Marlice C. Martelli; Samira M. L. Carvalho; Cleydson B. R. Santos; Antonio M. J. C. Neto; Davi S. B. Brasil (Medicinal Chemistry Research, 2019)

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

Modulation of antibiotic activity by the hydroalcoholic extract from leaves of Caryocar coriaceum WITTM - Luís J. de Lacerda Neto; A. G. B. Ramos; M. R. Kerntopf; H. D. M. Coutinho; L. J. Quintans-Junior; J. R. G. S. Almeida; J. Ribeiro-Filho; I. R. A. Menezes (Natural Product Research, 2018)

Ticks (Acari: Ixodidae) of the state of Amazonas, Brazil - Sergio L. Gianizella; Thiago F. Martins; Valeria C. Onofrio; Nair O. Aguiar; Waleska Gravena; Carlos A. R. do Nascimento; Laérzio C. Neto; Diogo L. Faria; Natália A. S. Lima; Monica R. Solorio; Louise Maranhão; Ivan J. Lima; et al. (Experimental and Applied Acarology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Structural and ultrastructural characterization of the spermatozoa in Pachycondyla striata and P. marginata - L. Cuquetto-Leite; H. Dolder; P. S. Oliveira; N. B. Espírito Santo; J. Lino-Neto; K. C. Mancini (Insectes Sociaux, 2017)

Influence of the current density on the electrochemical treatment of concentrated 1-butyl-3-methylimidazolium chloride solutions on diamond electrodes - Suzana M. L. de Oliveira Marcionilio; Gisele M. Alves; Rachel B. Góes e Silva; Pablo J. Lima Marques; Poliana D. Maia; Brenno A. D. Neto; José J. Linares (Environmental Science and Pollution Research, 2016)

Neonatal Candidemia Caused by Candida haemulonii: Case Report and Review of Literature - Carolina M. Silva; Ana M. R. Carvalho-Parahym; Danielle P. C. Macêdo; Reginaldo G. Lima-Neto; Elaine C. Francisco; Analy S. A. Melo; Maria da Conceição M. Silva; Moacir B. Jucá; Luciana R. B. Mello; Rosemary M. J. Amorim; Rejane P. Neves (Mycopathologia, 2015)

Surveillance of Azole Resistance Among Candida spp. as a Strategy for the Indirect Monitoring of Freshwater Environments - Raimunda S. N. Brilhante; Manoel A. N. Paiva; Célia M. S. Sampaio; Débora S. C. M. Castelo-Branco; Lucas P. Alencar; Tereza J. P. G. Bandeira; Rossana A. Cordeiro; Waldemiro de Aquino Pereira Neto; José L. B. Moreira; José J. C. Sidrim; Marcos F. G. Rocha (Water, Air, & Soil Pollution, 2015)

Hylax bahiensis Bechyné (Chrysomelidae: Eumolpinae): a New Potential Pest of Eucalyptus and Species Used for Atlantic Rainforest Restoration - R G Mafia; J B da Silva; J F Ramos; G V Mafia; G H Rosado-Neto; E M O Ferronatto (Neotropical Entomology, 2015)

Water Deficit and Salt Stress Diagnosis Through LED Induced Chlorophyll Fluorescence Analysis in Jatropha curcas L. - E. A. Silva; A. S. Gouveia-Neto; R. A. Oliveira; D. S. Moura; P. C. Cunha; E. B. Costa; T. J. R. Câmara; L. G. Willadino (Journal of Fluorescence, 2012)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

The potential for hydrocarbon biodegradation and production of extracellular polymeric substances by aerobic bacteria isolated from a Brazilian petroleum reservoir - S. P. Vasconcellos; B. M. Dellagnezze; A. Wieland; J.-H. Klock; E. V. Santos Neto; A. J. Marsaioli; V. M. Oliveira; W. Michaelis (World Journal of Microbiology and Biotechnology, 2011)

Solid Dispersions of Imidazolidinedione by PEG and PVP Polymers with Potential Antischistosomal Activities - Francimary L. Guedes; Boaz G. de Oliveira; Marcelo Z. Hernandes; Carlos A. De Simone; Francisco J. B. Veiga; Maria do Carmo A. de Lima; Ivan R. Pitta; Suely L. Galdino; Pedro José Rolim Neto (AAPS PharmSciTech, 2011)

Effectiveness of Scat‐Detection Dogs in Determining Species Presence in a Tropical Savanna Landscape - CARLY VYNNE; JOHN R. SKALSKI; RICARDO B. MACHADO; MARTHA J. GROOM; ANAH T. A. JÁCOMO; JADER MARINHO‐FILHO; MARIO B. RAMOS NETO; CRISTINA POMILLA; LEANDRO SILVEIRA; HEATH SMITH; SAMUEL K. WASSER (Conservation Biology, 2011)
Most protected areas are too small to sustain populations of wide‐ranging mammals; thus, identification and conservation of high‐quality habitat for those animals outside parks is often a high priority, particularly for regions where extensive land conversion is occurring. This is the case in the vicinity of Emas National Park, a small protected area in the Brazilian Cerrado. Over the last 40 years the native vegetation surrounding the park has been converted to agriculture, but the region still supports virtually all of the animals native to the area. We determined the effectiveness of scat‐detection dogs in detecting presence of five species of mammals threatened with extinction by habitat loss: maned wolf ( Chrysocyon brachyurus ), puma ( Puma concolor ), jaguar ( Panthera onca ), giant anteater ( Myrmecophaga tridactyla ), and giant armadillo ( Priodontes maximus ). The probability of scat detection varied among the five species and among survey quadrats of different size, but was consistent across team, season, and year. The probability of occurrence, determined from the presence of scat, in a randomly selected site within the study area ranged from 0.14 for jaguars, which occur primarily in the forested areas of the park, to 0.91 for maned wolves, the most widely distributed species in our study area. Most occurrences of giant armadillos in the park were in open grasslands, but in the agricultural matrix they tended to occur in riparian woodlands. At least one target species occurred in every survey quadrat, and giant armadillos, jaguars, and maned wolves were more likely to be present in quadrats located inside than outside the park. The effort required for detection of scats was highest for the two felids. We were able to detect the presence for each of five wide‐ranging species inside and outside the park and to assign occurrence probabilities to specific survey sites. Thus, scat dogs provide an effective survey tool for rare species even when accurate detection likelihoods are required. We believe the way we used scat‐detection dogs to determine the presence of species can be applied to the detection of other mammalian species in other ecosystems.

Viability and cell cycle analysis of equine fibroblasts cultured in vitro - J. F. Lima-Neto; C. B. Fernandes; M. A. Alvarenga; M. A. Golim; F. C. Landim-Alvarenga (Cell and Tissue Banking, 2010)

Burkholderia species are ancient symbionts of legumes - CYRIL BONTEMPS; GEOFFREY N. ELLIOTT; MARCELO F. SIMON; FÁBIO B. DOS REIS JÚNIOR; EDUARDO GROSS; REBECCA C. LAWTON; NICOLAU ELIAS NETO; MARIA de FÁTIMA LOUREIRO; SERGIO M. DE FARIA; JANET I. SPRENT; EUAN K. JAMES; J. PETER W. YOUNG (Molecular Ecology, 2010)

Decolorization of synthetic dyes by basidiomycetes isolated from woods of the Atlantic Forest (PE), Brazil - E. S. Lyra; K. A. Moreira; T. S. Porto; M. N. Carneiro da Cunha; F. B. Paz Júnior; B. B. Neto; J. L. Lima-Filho; M. A. Q. Cavalcanti; A. Converti; A. L. P. Porto (World Journal of Microbiology and Biotechnology, 2009)

The native Palythoa caribaeorum overgrows on invasive species in the intertidal zone - J. P. Mendonça-Neto; B. A. P. da Gama (Coral Reefs, 2009)

Linkage to chromosome 2q36.1 in autosomal dominant Dandy-Walker malformation with occipital cephalocele and evidence for genetic heterogeneity - Ali Jalali; Kimberly A. Aldinger; Ajit Chary; David G. Mclone; Robin M. Bowman; Luan Cong Le; Phillip Jardine; Ruth Newbury-Ecob; Andrew Mallick; Nadereh Jafari; Eric J. Russell; John Curran; et al. (Human Genetics, 2008)

Proteome analysis of embryogenic cell suspensions of cowpea (Vigna unguiculata) - F. C. S. Nogueira; E. F. Gonçalves; E. S. Jereissati; M. Santos; J. H. Costa; O. B. Oliveira-Neto; A. A. Soares; G. B. Domont; F. A. P. Campos (Plant Cell Reports, 2007)

Acute cattle intoxication from Nerium oleander pods - B. Soto-Blanco; J. D. Fontenele-Neto; D. M. Silva; P. F. C. C. Reis; J. E. Nóbrega (Tropical Animal Health and Production, 2006)

Milk-clotting protease production by Nocardiopsis sp. in an inexpensive medium - M. T. H. Cavalcanti; C. R. Martinez; V. C. Furtado; B. B. Neto; M. F. Teixeira; J. L. Lima Filho; A. L. F. Porto (World Journal of Microbiology and Biotechnology, 2005)

Observing bacterial activity interferometrically - D. Faragó Jardim; R. Batista Santiago Neto; R. R. P. Machado; F. M. Aarestrup; J. P. R. F. de Mendonça; B. Lesche (European Biophysics Journal, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Zinc acutely and temporarily inhibits adrenal cortisol secretion in humans - J. Brandão-Neto; B. B. de Mendonça; T. Shuhama; J. S. Marchini; W. P. Pimenta; M. T. T. Tornero (Biological Trace Element Research, 1990)